Bridging Small Molecules to Modified Bacterial Microparticles Using a Disulphide Linkage: MIS416 as a Cargo Delivery System. - Francesco Mainini; David S Larsen; Gill A Webster; Sarah L Young; Michael R Eccles (PLoS ONE)
MIS416 is an intact minimal cell wall skeleton derived from Proprionibacterium acnes that is phagocytosed by antigen presenting cells, including dendritic cells (DCs). This property allows MIS416 to be exploited as a vehicle for the delivery of peptide antigens or other molecules (for example, nucleic acids) to DCs. We previously showed that covalent (non-cleavable) conjugation of OVA, a model antigen derived from ovalbumin, to MIS416 enhanced immune responses in DCs in vivo, compared to unconjugated MIS416 and OVA. Intracellular trafficking promotes the lysosomal degradation of MIS416, leading to the destruction of MIS416 plus the associated cargos conjugated to MIS416. However, lysosomal degradation of cargo may not be desired for some MIS416 conjugates. Here we have investigated whether a cleavable linkage could facilitate release of the cargo in the cytoplasm of DCs to avoid lysosomal degradation. DCs were treated in vitro with disulfide-containing conjugates, and as hypothesised faster release of SIINFEKL peptide in the cytoplasm of DCs was observed with the inclusion of a disulfide bond between MIS416 and cargo. The inclusion of a cleavable disulfide bond in the conjugates did not significantly alter the amount of SIINFEKL antigens presented on MHC I molecules on DCs as compared with conjugates without a disulfide bond. However, the conjugates containing disulfide-linkages performed either slightly better (p<0.05) than, or the same as conjugates without a disulfide bond with respect to in vitro OT-1 T-cell proliferation induced by the presentation of SIINFEKL antigens on DCs, or DC activation studies, respectively. However, disulfide-containing conjugates were less effective than conjugates without a disulfide bond in in vivo cytotoxicity assays. In conclusion, inclusion of a disulfide bond in MIS416-peptide conjugates was associated with efficient release of peptides in the cytoplasm of DCs, an important consideration for MIS416-mediated delivery of degradation-sensitive cargoes. However, treatment of DCs with disulfide-containing conjugates did not significantly alter the presentation of peptide antigens on MHC class I molecules to T-cells, or greatly enhance antigen-associated T-cell proliferation in vitro.